1999
DOI: 10.1046/j.1365-3156.1999.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of health workers in an era of cost sharing: Ghana's drug cash and carry system

Abstract: SummaryThis qualitative study aimed to assess possible changes in prescription patterns and resultant implications for the quality of care delivered in three southern districts of Ghana after the introduction of a full cost recovery scheme for drugs in 1992. While the availability of safe and effective drugs has improved especially in rural areas, not all patients are able to meet the cost for required medication. This has influenced the behaviour of most prescribers, who now take economical limitations into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Consistently, another study in eastern Tanzania found a considerable proportion of pregnant women being unaware of IPTp, including its uptake and the timing of the correct doses, despite attending ANC clinics (Brieger 2008). Therefore, answers collected based on opinions given by respondents through word of mouth without other mechanisms being used to confirm them need to be treated cautiously (Asenso-Okyere et al, 1999). However, these latter findings/evidence are validated by reports from the frontline HWs in the present study who confessed to have occasionally found themselves too busy with heavy workload at HFs to deliver the required health messages or keep individual clients' records for the services delivered in the appropriate official registers or personal HF cards (Mubyazi et al, 2012;Mubyazi et al, 2014a).…”
Section: Anc-seeking Behaviour Influenced By Knowledge Of the Servicementioning
confidence: 64%
“…Consistently, another study in eastern Tanzania found a considerable proportion of pregnant women being unaware of IPTp, including its uptake and the timing of the correct doses, despite attending ANC clinics (Brieger 2008). Therefore, answers collected based on opinions given by respondents through word of mouth without other mechanisms being used to confirm them need to be treated cautiously (Asenso-Okyere et al, 1999). However, these latter findings/evidence are validated by reports from the frontline HWs in the present study who confessed to have occasionally found themselves too busy with heavy workload at HFs to deliver the required health messages or keep individual clients' records for the services delivered in the appropriate official registers or personal HF cards (Mubyazi et al, 2012;Mubyazi et al, 2014a).…”
Section: Anc-seeking Behaviour Influenced By Knowledge Of the Servicementioning
confidence: 64%
“…Though there have been various concerns about the attitude and behaviour of nurses and the need for change of attitude, most studies only investigated the prevalence of the unhealthy attitude and whether the attitude has changed over time (Asenso-Okyere et al, 1999). There has not been any systematic and pragmatic intervention to deal with the situation in Ghana.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In general, patients did not speak well of nurses. As observed by Asenso-Okyere et al (1999), the general opinion was that nurses did not treat patients well and in some cases were rude to them. Some people are of the view that present day nurses do not care whether you are paying for the treatment or not, and that they do not work for the love of the vocation any longer.…”
Section: Explanations For Nurses' Attitudementioning
confidence: 99%
“…The tendency has been to look at the performance of the health staff after decentralization and related changes (Asenso-Okyere et al, 1999) or at the problems of managing them as 'human resources' (Saide and Stewart, 2001). That is, health workers are seen as a means to an end: health care.…”
Section: Introductionmentioning
confidence: 99%